ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF SPASIAL MATERI GEOMETRI DI SMA MUHAMMADIYAH 1 PURBALINGGA - Septiana Dwi Melinda (AlphaMath : Journal of Mathematics Education, 2017)
This study aimed to analyze the students’ mathematical representation ability viewed from spatial cognitive style on geometry. This study used qualitative method. Subjects in this study were students X,MIPA 1 SMA Muhammadiyah 1 Purbalingga. The sampling technique of this study was GEFT (Group Embedded Figure Test) by taking three students for a group of high spatial cognitive sytle, 3 students for a group of medium spatial cognitive sytle, and 3 students for a group of low spatial cognitive sytle. Data analysis techniques used in this study were reduction of data (data reduction), description of data (data display) and conclusion (verification). Data collection techniques in this study were tests, interviews, and documentation. The results of this study indicate that high spatial cognitive style group is able to master three indicators of representation, those are: recording and communicating mathematical ideas in the from of symbol or picture on geometry using the words/ written text in solving geometry problems as well as creating mathematical model from the ideas by applying mathematical expressions in solving geometry problems. While medium spatial cognitive style group is able to master two indicators, those are: recording and communicating mathematical ideas in the from of geometry symbol/image and written words written texts in solving geometry problems. In addition, the low spatial cognitive style group is able to master an indicator that is recording and communicating mathematical ideas in the from of geometry symbol or picture. Keywords: Mathematical Representation Ability, Spatial Cognitive Style